(untitled) (University of Khartoum Journal of Agricultural Sciences, 2022)
This study aimed to survey, characterize, and identify the causal pathogen of tomato bacterial spots (TBS). The survey evaluated the disease incidence and severity on tomato cultivated in Blue Nile State during the autumn season 2015. The surveyed sites were in Alrosseris and Aldmazein localities. Four farms were selected from each locality. Symptomatic leaves were collected and sent to plant pathology laboratory, Department of Crop protection, Faculty of Agriculture, University of Khartoum for detection of the pathogen. Pathogenicity of the isolated bacteria was confirmed by relevant test. The pathogen was isolated and characterized morphologically, biochemically and at molecular level. The survey revealed that there was no significant difference in disease incidence within each locality, while there were significant differences (P ≤ 0.05) among locations within both localities in disease severity. The disease incidence was remarkably high in Alrosseris and Aldamazein which recorded 49.27 and 52.17 %, respectively, while the disease severity was 28.28 and 30.32%, respectively. The results showed that the isolates were rod shaped, obligate aerobic, Gram negative, catalase positive, oxidase negative, and were able to hydrolyse starch and gelatine, yellow colonies on nutrient agar and Yeast Dextrose Calcium carbonate (YDC) media. In the pathogenicity test, the bacterium known as Xanthomonas vesicatoria was confirmed to be as Xanthomonas euvesicatoria by PCR and sequence analysis of the 16S RNA gene (Gen Bank Accession No’s MH047248, MH051263 and MG686236).These results also indicate that the tomato plants grown in Blue Nile State were highly infected by the bacterial leaf spots. Further studies should be considered to determine potential yield loss caused by the pathogen, as well as control strategies to limit the spread of this pathogen. To our knowledge, this is the first report of Xanthomonas euvesicatoria causing bacterial spot disease in tomato in Sudan